Hybrid Rotor Noise Optimization - Philipp Mandl; Laura Babetto; Eike Stumpf; Christian Breitsamter (Engineering Proceedings, 2025)
This study examines noise reduction strategies for unmanned aerial vehicles (UAVs) in urban air mobility applications, with a particular focus on package delivery. By employing a combination of low-, mid- and high-fidelity aerodynamic and aeroacoustic analyses, this research investigates the impact of rotor design parameters, including blade spacing and rotational speed, on noise emissions. The results demonstrate that an increase in rotor spacing results in a reduction in noise emissions. By adjusting the blade chord and twist within an optimization loop, it was possible to decrease tonal noise, yielding a Sound Pressure Level (SPL) reduction of about 3.51 dB while improving propulsive efficiency by 39%. These findings highlight the importance of rotor geometry optimisation during the early design stages in order to meet both performance and noise requirements.